Learning Multimedia Development Using Articulate Storyline for Students - Nugroho, Fandi; Arrosyad, Muhammad Iqbal (International Journal of Elementary Education, 2020)
The implementation of learning in elementary schools is very limited to learning media and more teacher-centred learning. This study aims to develop multimedia learning using articulated storylines that are feasible and effective for fourth-grade students of SD Muhammadiyah Pangkalpinang. This type of research is Research and Development (R&D). This research development stage refers to the Alessi & Trollip development model, which is divided into four stages, namely: (1) planning; (2) design; (3) product development, and (4) evaluation. Determination of the feasibility level based on the validation test of media and material experts and testing to 6 students through a questionnaire. Determination of the level of effectiveness based on pre-test and post-test data to 30 students. The results showed that the average feasibility level of the assessment percentage by the media expert validator was 82.5% with the "Very Good" category. Expert assessment of the material is 71%, with the category "Very Good". The responses of 6 students get an average final score in the percentage of 71.33% in the "Very Good" category. Based on the pre-test and post-test mean, there is an increase in the mean score of 14.9. The mean value obtained is then converted to the calculation of the gain score to determine the level of product effectiveness. Overall, in calculating the gain score, the mean value was 0.62 for 30 students in the "Medium" category. It can be concluded that integrative thematic multimedia learning on sub-themes of animal and plant diversity for fourth-grade elementary school is feasible and effective to use.